Mandatory Seatbelt Laws and Traffic Fatalities: A Reassessment - D. Mark Anderson; Yang Liang; Joseph J. Sabia (Institute of Labor Economics (IZA), 2022)
Using data from the Fatality Analysis Reporting System for the period 1983-1997, Cohen and Einav (Review of Economics and Statistics 2003; 85(4): 828–843) found that mandatory seatbelt laws were associated with a 4 to 6 percent reduction in traffic fatalities among motor vehicle occupants. After successfully replicating their two-way fixed effects estimates, we (1) add 22 years of data (1998-2019) to capture additional seatbelt policy variation and observe a longer post-treatment period, (2) employ the interaction-weighted estimator proposed by Sun and Abraham (2021) to address potential bias due to heterogeneous and dynamic treatment effects, and (3) estimate event-study models to investigate pre-treatment trends and explore lagged post-treatment effects. Consistent with Cohen and Einav (2003), our updated estimates show that primary seatbelt laws are associated with a 5 to 9 percent reduction in fatalities among motor vehicle occupants. Estimated effects of secondary seatbelt laws are smaller in magnitude and sensitive to model choice.
Keywords: C13; I12; K32; K42; 330; mandatory seatbelt laws; traffic fatalities; traffic safety